Extensive in silico analysis of Mimivirus coded Rab GTPase homolog suggests a possible role in virion membrane biogenesis - Zade, Amrutraj; Sengupta, Malavi; Kondabagil, Kiran (Frontiers in Microbiology, 2015)
Rab GTPases are the key regulators of intracellular membrane trafficking in eukaryotes. Many viruses and intracellular bacterial pathogens have evolved to hijack the host Rab GTPase functions, mainly through activators and effector proteins, for their benefit. Acanthamoeba polyphaga mimivirus (APMV) is one of the largest viruses and belongs to the monophyletic clade of nucleo-cytoplasmic large DNA viruses (NCLDV). The inner membrane lining is integral to the APMV virion structure. APMV assembly involves extensive host membrane modifications, like vesicle budding and fusion, leading to the formation of a membrane sheet that is incorporated into the virion. Intriguingly, APMV and all group I members of the Mimiviridae family code for a putative Rab GTPase protein. APMV is the first reported virus to code for a Rab GTPase (encoded by R214 gene). Our thorough in silico analysis of the subfamily specific (SF) region of Mimiviridae Rab GTPase sequences suggests that they are related to Rab5, a member of the group II Rab GTPases, of lower eukaryotes. Because of their high divergence from the existing three isoforms, A, B and C of the Rab5-family, we suggest that Mimiviridae Rabs constitute a new isoform, Rab5D. Phylogenetic analysis indicated probable horizontal acquisition from a lower eukaryotic ancestor followed by selection and divergence. Furthermore, interaction network analysis suggests that vps34 (a Class III P13K homolog, coded by APMV L615), Atg-8 and dynamin (host proteins) are recruited by APMV Rab GTPase during capsid assembly. Based on these observations, we hypothesize that APMV Rab plays a role in the acquisition of inner membrane during virion assembly.